2004
DOI: 10.1007/s00436-004-1274-6
|View full text |Cite
|
Sign up to set email alerts
|

The failure of Haemonchus contortus excretory/secretory products to stimulate gastrin secretion in vitro

Abstract: Excretory/secretory (ES) products collected from exsheathed L3 or parasitic stages of Haemonchus contortus were tested in vitro for gastrin stimulatory properties using an ovine abomasal antral mucosal preparation. In addition, the motility of exsheathed L3 and parasites recovered on weeks 2, 6 and 8 post-infection was studied in water, saline, saline with glucose or ovine blood and in HBSS pH 2.5-7.4. Parasitic stages became immotile rapidly in water and HBSS pH 2.5, more slowly in HBSS pH 3.5, but nearly 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In contrast, ES products of H . contortus [ 73 ] or T . circumcincta [ 74 ] were ineffective in stimulating gastrin secretion by the G-cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ES products of H . contortus [ 73 ] or T . circumcincta [ 74 ] were ineffective in stimulating gastrin secretion by the G-cell.…”
Section: Discussionmentioning
confidence: 99%
“…contortus [ 104 ]. Alternatively, loss of the mucus layer may be detrimental to the parasites and favour worm expulsion, as luminal worm stages are sensitive to acid in vitro [ 73 , 74 ]. Worms living in the mucus appear to be protected by bicarbonate ions normally secreted by the SMC into the mucus, creating a pH gradient between the neutral epithelial surface and the acidic lumen to protect the mucosa from acid and pepsin damage [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with adult worms of both H. contortus and Ostertagia spp. have reported that motility is maintained for extended periods at pH 4.5 and above rather than at low pH, whereas exsheathed L3 of both species remained motile for days at pH 2.5 (Eiler et al 1981;Haag 1995;Lawton et al 2002). Therefore, it is also possible that larval stages may release different products at a lower pH (Lawton et al 2002), whereas the medium used in these studies was routinely adjusted to a pH of 7.4.…”
Section: Discussionmentioning
confidence: 89%
“…This, together with the observation that ES products from adult H. contortus inhibit aminopyrine accumulation by isolated rabbit gastric glands (Merkelbach et al 2002), suggests that excreted or secreted products of the parasites may interfere directly with parietal cell function (Anderson et al 1985;Simpson et al 1997;Scott et al 2000) and also that this activity might be common to ES products derived from different lifecycle stages. The mechanisms responsible remain uncertain but seem to be a crucial step for host pathology as well as worm survival (Haag 1995;Stringfellow 1986). In addition, low pH is not optimal for adult worm fecundity (Honde and Bueno 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Parasite ES products involved in the host-parasite interaction, particularly those which facilitate the establishment and maintenance of the parasite in the host, are attractive candidates for anthelmintic therapies. Unlike L3, L4 and adult worms of the sheep abomasal nematode parasites Ostertagia (Teladorsagia) circumcincta and Haemonchus contortus are rapidly killed in vitro at pH 2.5 and 3.5 (Haag 1995;Lawton et al 2002), suggesting that the typical inhibition of acid secretion in the parasitised abomasum may be beneficial to the worms.…”
Section: Introductionmentioning
confidence: 92%